The Practicality of Prezi Media in the PBL Model for Pancasila Education at SDN 06 Taluk - Ramli, Natasya; Reinita, Reinita; Desyandri, Desyandri; Anita, Yesi (Journal of Innovation and Research in Primary Education, 2025)
Today's teachers want interactive and dynamic learning medium, which prompted this research. This project will use Prezi and Problem-Based Learning (PBL) to educate fourth-graders in primary schools Pancasila Education. The need for innovative learning tools that boost students' interest and understanding inspired this medium. Fourth-graders at SDN 06 Taluk were tested. Data was collected via observations, interviews, and practical tools. These steps are needs analysis, instructional media design and product creation, implementation of the learning media, and evaluation of the created media's performance. The teacher and student practicality surveys for the Prezi media at SDN 06 Taluk showed that 96% of teachers and 92.1% of students thought it was useful. Further, both instructors and students have commented on how useful and simple this learning medium is for teaching Pancasila Education. The PBL methodology, which emphasises problem solving that is relevant to students' experiences, has been shown to improve critical thinking skills. Consequently, Prezi learning media may serve as an alternative to enhance the quality of Pancasila Education instruction in elementary institutions.